Analisis Peran Alat Bukti dan Keterangan Saksi dalam Menentukan Keputusan Pengadilan Pidana - Jojor Cristina; Indri Manalu (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
One of the essential aspects of the criminal justice process is evidence, in which both physical evidence and witness testimony play a central role in shaping the judge's conviction. However, a legal issue arises regarding the evidential strength of witness testimony compared to other types of evidence in influencing judicial decisions. This study aims to analyze the role and legal strength of evidence and witness testimony in criminal proceedings based on the provisions of the Indonesian Criminal Procedure Code (KUHAP) and judicial practices in Indonesia. The research employs a normative juridical method with a statutory approach and case studies of several court decisions. The results indicate that judges tend to give significant evidential weight to witness testimony when supported by other valid evidence, such as documents, indications, or defendant statements. However, if witness testimony stands alone without supporting evidence, its probative value becomes weak and insufficient to convince the judge. Therefore, the integration of physical evidence and witness testimony is a crucial factor in ensuring justice and legal certainty in criminal verdicts.